Electron population of impurity atoms in crystal in external quantizing magnetic field - Lukiyanets, B.A. (Condensed Matter Physics, 2002)
The model which is discussed permits to describe the charge state of the
impurity both at the intercalation of a layer crystal and at the adsorption on
a crystal surface. In the framework of the model, the influence of the external
quantizing magnetic field on the magnitude of charge population of the
impurity is analyzed. The obtained results indicate that the external magnetic
field is an important factor that influences the effects of adsorption or
intercalation. Обговорюється модель, яка дозволяє описувати зарядовий стан домішкового атома як в явищі інтеркалювання шаруватого кристалу, так і в явищі адсорбції на кристалічній поверхні. В рамках моделі аналізується вплив зовнішнього квантуючого магнітного поля на величину електронного заповнення такого атома. Отримані результати дозволяють розглядати зовнішнє магнітне поле як істотний фактор впливу на явище адсорбції і інтеркаляції.